RESPON PERSERIKATAN BANGSA-BANGSA DALAM MENYELESAIKAN KASUS PELANGGARAN HAM DI MYANMAR TAHUN 2015-2020 - Ryan Rizky Ramadhan (2024)
Human rights in Myanmar under its military rule regime have long been considered among the worst in the world. Several international human rights organizations have repeatedly documented and condemned widespread human rights violations in Myanmar. Forced labor, human trafficking and child labor are commonplace. The Burmese government regime and military junta are also notorious for the rampant use of sexual violence as a means of control, including allegations of systematic rape and the taking of sex slaves by the military. The security forces in Myanmar committed serious violations of international law that warrant criminal investigation and prosecution, namely crimes against humanity, war crimes and genocide. This research aims to discuss the background and causes of the emergence of cases of human rights violations in Myanmar, as well as the response and policies of the United Nations to cases of human rights violations in the region. The method used is descriptive qualitative using primary and secondary data sources. Data retrieval techniques are carried out through literature studies and through data analysis techniques. Researchers used four stages of data analysis, namely data collection, data reduction, data presentation and data withdrawal/verification. The final results of this study can be utilized as a reading reference for general and specific, namely researchers and academics in the field of International Relations studies, especially in cases of human rights violations.